2017
DOI: 10.16965/ijar.2016.451
|View full text |Cite
|
Sign up to set email alerts
|

Knee Cap: A Morphometric Study

Abstract: Background: The patella is the largest sessamoid bone embedded in the tendon of quadriceps femoris. Patella although not distinct for determining sex or race it is used for personal identification as it is resistant to post mortem changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…In the present study mean height of the patella was 39.07mm with standard deviation of 4.45 which was similar to the findings of Shang peng, Magi Murugan, Vohra et al but less compared to the previous study by Schlenzka and Schwesinger. [6][7][8][9] Table 1 also shows that, the values of patellar height are comparable with previous studies irrespective of the methodology (CT, Dry bones/MRI). However, the width of patella in our study was also less compared to study by Schlenzka and schwesinger 9 but almost similar to the study by Poonam Vohra et al and Iranpour et al 5,8 These variations could be because of racial differences, differences in methodology, sex etc.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study mean height of the patella was 39.07mm with standard deviation of 4.45 which was similar to the findings of Shang peng, Magi Murugan, Vohra et al but less compared to the previous study by Schlenzka and Schwesinger. [6][7][8][9] Table 1 also shows that, the values of patellar height are comparable with previous studies irrespective of the methodology (CT, Dry bones/MRI). However, the width of patella in our study was also less compared to study by Schlenzka and schwesinger 9 but almost similar to the study by Poonam Vohra et al and Iranpour et al 5,8 These variations could be because of racial differences, differences in methodology, sex etc.…”
Section: Discussionsupporting
confidence: 84%
“…5 The ratio of LAF to MAF was 1.24mm similar to studies by Shang Peng (1.34mm) and Magi Murugan (1.21mm). 6,7 No significant differences in variable values were observed between the right and left side similar to previous studies However, study by Olateju reported greater width and thickness of patella on the right in Europeans which he postulated was because of over use of one limb. 14 We observed Type B patella as the most common variant based on Wibergs classification similar to Magi Murugan and Fucentese et.al.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, a study conducted in central India by Upadhyay et al 12 reported similar mean values for patellar height, width, and thickness. Similarly, Murugan et al 13 conducted a morphometric study of the kneecap and reported similar results for the parameters analyzed in their study. Additionally, Ahmed and Mohammed-L 14 conducted a study on Japanese ethnicity and reported similar results for patellar morphometry and volumetry.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, the mean patella length (L1) was 3.45 cm (ranging from 3.05-4.52 cm), which corresponds to smaller patella size compared to the values published in the literature [8,9,18,37]. Previous reports on the double bundle MPFL reconstruction techniques describe tunnel placement in the upper half of the patella and distance between tunnels to be at least 1 cm [16,27,[29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 46%